Strategi dan Tantangan Pengembangan Karakteristik Guru Profesional dalam Meningkatkan Mutu Pendidikan berdasarkan Perspektif Jean Piaget - Hidayatul Maulidiyah; Abdullah Fathoni Sujada; Imam Syafii (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
The development of professional teacher characteristics is a key factor in improving the quality of education. This article analyzes the strategies, challenges, and implications of teacher professional development based on Jean Piaget's perspective. Piaget's cognitive development theory provides a foundation for understanding how teachers can adapt teaching methods to the developmental stages of students. In this study, various strategies are applied to improve teacher competence, including pedagogical training oriented towards students' cognitive development, experiential learning, and critical reflection on teaching practices. However, there are challenges such as limited access to quality training, resistance to changes in learning methods, and lack of institutional support. This article also discusses the implications of the development of professional teacher characteristics for improving the quality of education, especially in creating a learning environment that is in accordance with students' developmental needs. By understanding and applying Piaget's principles, teachers can be more effective in guiding students towards deeper and more meaningful understanding. In compiling this article, we used a qualitative method by taking a literature approach, namely by collecting as many reference sources as possible and taking data from references related to the title that the author raised. This article aims to examine effective strategies in building professional teacher characteristics, identify challenges that arise in the implementation process, and analyze the implications of improving the quality of education based on Jean Piaget's perspective